Endocrine manifestations of ovarian lesions in children: an 11 year review - de Silva, K.S.H.; Warne, G.L. (My University, 2001)
Objective To describe the clinical and ultrasonographic features of children with ovarian lesions presenting with endocrine manifestations. Method The records of patients under 12 years of age with ovarian lesions admitted to the Royal Children's Hospital in Melbourne, Australia during an 11 year period were retrospectively reviewed. Patients presenting with endocrine manifestations were identified and further analysed. Results Out of 49 patients < 12 years of age presenting with ovarian lesions, 7 had endocrine manifestations. Their ages ranged from 6 months to 11.6 years. 3 patients each had early onset of puberty and precocious puberty while one had evidence of virilisation. These were found in association with both benign and malignant ovarian lesions. A palpable abdominal mass was found in 3 patients. The size of the lesion on ultrasound scan was recorded in 4 patients and the consistency in 6. Two patients had lesions >10 cm and in 3 the consistency was recorded as being complex (cystic and solid). Conclusion Endocrine manifestations associated with ovarian lesions are rare in children. But a girl presenting with abnormal pubertal changes should be evaluated carefully as these features can be associated with benign and malignant tumours of the ovary as well as with physiological cysts.